The Penguatan Literasi Kepada Anak Melalui Perpustakaan Rumah Ibadah di Desa Lagan Kecamatan Semidang Lagan Kabupaten Bengkulu Tengah: Interest in Literacy - pasaribu, derliana; Nurwiana; Rahmat Fadhli; Ahmad Syarifin (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
The article discusses the significant role of libraries in houses of worship in increasing children’s interest in literacy in literacy. Such libraries are not only recognized as facilities for religious activities, but also serve as a means to develop children’s literacy skills in various aspects of their lives. The purpose of this article is to explore the ways in which a house of worship libraries can be a fun and educational environment for children to learn to read, write and explore knowledge. Utilization of a house of worship library in increasing literacy interest in children requires an approach that combine religious aspects with literacy activities. Research shows that a calm and focused atmosphere in a house of worship library can help create conditions that support children’s learning. help create conditions that support children’s learning. In addition, such libraries can also play a role in expanding children’s knowledge of children’s knowledge of religious values while strengthening their literacy skills literacy skills. By encouraging the use houses of worship as literacy centers, it is hoped that children will be increasingly interested in reading and learning as a whole. These benefits will not only have a positive impact on their personal development but also on the community in which they live. in which they live. This article gathers evidence and views from various sources to show the great potential of ibadah home libraries.